In Situ Nondestructive Identification of Natural Dyes in Ancient Textiles by Reflection Fourier Transform Mid-Infrared (FT-MIR) Spectroscopy. Issue 2 (February 2015) - De Luca, Eleonora; Bruni, Silvia; Sali, Diego; Guglielmi, Vittoria; Belloni, Paolo
Silk embroideries and cotton grounds of ancient Caucasian (Kaitag) textiles were analyzed in situ by a portable Fourier transform infrared (FT-IR) spectrometer equipped with a reflection module. Differently colored areas were analyzed for the purpose of identifying the dyes fixed on the fibers. The spectra so obtained were elaborated by calculating the corresponding second derivative, and a library search was then performed using a database including the second derivative spectra of a large range of historical dyes and the corresponding undyed fibers. The results presented here suggest that this technique, combined with the library search method, has a good capability of recognizing natural dyes on both types of ancient textile fibers, in an entirely nondestructive way.